What the ear hears (and doesn't) : inside the extraordinary everyday world of frequency - Mainwaring, Richard (Sourcebooks, 2023)
"In 2011, without warning, a skyscraper in South Korea began to shake uncontrollably and was immediately evacuated. Was it an earthquake? A terrorist attack? No one seemed quite sure. The actual cause emerged later: Twenty-three middle-aged Koreans were having a Tae Bo fitness class in the office gym on the twelfth floor. Their beats had inadvertently matched the building's natural frequency, and this coincidence caused the building to shake at an alarming rate for ten minutes. Frequency is all around us, but really isn't understood. What the Ear Hears (and Doesn't) reveals the extraordinary world of frequency-from medicine to religion to the environment to the paranormal-not through abstract theory, but through a selection of small memorable human (and animal) stories laced with dry humor, including: The elephant who anticipated the 2004 Asian tsunami and carried a young girl miles inland, saving her life; The reason for those deep spiritual feelings we have in churches; The cutting-edge methods that are changing medicine; The world's loneliest whale"--